Status Gizi Anak Baru Masuk Sekolah di Kota Denpasar - Suastiti, Ni Made Ayu (Community Health, 2013)
The proportion of newly enrolled elementary students at age 6-9 years in city of Denpasar in 2007 that consider as stunted was 36,1%. Proportion of thin boys was 9,2% and thin girls 7,4%. Meanwhile, boys and girls who were overweight was 18,3% and 11,5%, respectively. Newly enrolled elementary students are risk of getting nutritional problem either under or overweight. The aim of this study was to analyze the nutritional status of newly enrolled elementary students in City of Denpasar in 2011 based on antropometric indexes including weight for age, height for age and BMI for age. This was an observational study that applying cross sectional desigen. There ware 300 samples in the study that were selected by cluster random samplin method. The data for determining the nutritional status of the children was obtain and analyzed from report of the newly enrolled elementary students health screening in 2011. It than was presented in either table or description. It was found that based on BMI for age index more than half of the children 59,30% had normal nutritional status, 26,70% was overweight and 14,00% was undernourishhed.
Keywords: newly enrolled elementary students, body weight, nutritional status